The Correlation between Reading Fanfiction and Reading Interest among Senior High School Students - Shofa, Ghefira Zahira; Rahmawati, Yeni; Puspita, Rani Herning (Universitas PGRI Adi Buana Surabaya, 2026)
Reading interest remains a significant challenge for EFL learners in Indonesia, particularly at the senior high school level. This study aimed to examine the relationship between reading fanfiction and students' reading interest within an EFL context. Utilizing a quantitative correlational Research design, the study involved 348 students from grades X and XI at a public vocational high school in East Kalimantan. Data were collected using a structured questionnaire designed to assess students' engagement with fanfiction and their overall reading interest. The instrument demonstrated acceptable validity and reliability. Data analysis included descriptive statistics, normality testing using the Kolmogorov–Smirnov test, and Pearson Product–moment correlation analysis. The results indicated a strong and statistically significant positive correlation between overall engagement in reading fanfiction and reading interest (r = 0.792, p < 0.01). Furthermore, a significant positive relationship was observed between the frequency of fanfiction reading and reading interest (r = 0.620, p < 0.01). These findings suggest that students who engage frequently and meaningfully with fanfiction tend to demonstrate higher levels of reading interest. Unlike previous studies that have primarily focused on qualitative perspectives or examined the effects of fanfiction on reading comprehension and language skills among university students, this study provides quantitative evidence of the relationship between fanfiction reading and reading interest among senior high school EFL learners in the Indonesian context. The findings suggest that fanfiction can serve as an effective interest-based digital reading resource to promote voluntary reading behaviors and foster positive attitudes toward reading English texts.